The Impact of Keyword Technique on the Students’ Vocabulary Retention Ability in an EFL Class - Jenpattarakul, Win (Mediterranean Journal of Social Sciences, 2012)
This paper makes an effort to show the effectiveness of keyword technique as a vocabulary retention technique. The studywas a one-group pretest-posttest experiment and aimed to investigate the effect of keyword technique on vocabularies retention ability of40 Bangkok University students and explore their attitude towards the use of keyword technique. The instruments were the vocabularytests, and the questionnaire exploring attitude towards keyword technique. The pretest and posttest scores of the experimental groupwere calculated by descriptive statistics and compared by using a dependent t-Test measure. It was found that students obtained higherscores for the posttest than the pretest scores at the 0.05 level of significance. In addition, their attitude towards using the keywordtechnique was at a high level. Moreover, the results from this study supported that using keyword technique helped the students storeand retrieve a new bunch of vocabularies, motivated them to learn English language and expanded their imagination and creativity.Pedagogical implications into vocabulary retention technique were suggested.